Serve the power(s), serve the state : America and Eurasia - Garavaglia, Juan Carlos; Braddick, M. J. (Michael J.), 1962-; Lan, Keli, 1950- (Cambridge Scholars Publishing, 2016)
Examines the organization and consolidation of various groups acting to create newly emergent forms of social and political power.